A Study of New Class of Star-Like Functions Associated by Symmetric p,q-Calculus - Khalid Akbar (Hindawi Limited, 2021)
As of late quantum calculus is broadly utilized in different parts of mathematics. Uniquely, the hypothesis of univalent functions can be newly portrayed by utilizing q-calculus. In this paper, we utilize our recently presented symmetric p,q-number m˜ p,q to characterize new symmetric p,q-derivative D p,q of analytic function f in the open unit disk U. Utilizing D p,q, we introduce new class of analytic star-like functions and examine some fascinating results.